Channeling the final Say in Politics - Hans Gersbach; Stephan Imhof; Oriol Tejada (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
We examine how the final say in a sequence of proposals for local public project provision, financing, and redistribution can be channeled towards socially desirable outcomes, thereby breaking the dictatorial power of the last agenda-setter. Individuals are heterogeneous with some citizens benefiting from the public project (winners) and the rest losing (losers) relative to per-capita costs. Our main insight is that a simple ban on subsidies for the proposal-makers can achieve the purpose whenever the first proposal-maker is a winner and the second proposal-maker is a loser. Such a ban induces project winners to make efficient public project proposals that are however coupled with socially undesirable subsidy schemes. The best possible amendment for project losers is then to match the project proposal and to eliminate all subsidies. We further show that two-round proposal-making constitutes the minimal form of political competition yielding first-best outcomes and that restrictions on tax schemes are socially desirable.
Keywords: Q38; F12; H20; H70; 330; Voters & Elections; Game Theory; Social Choice & Welfare; Kommunalpolitik; Kommunalrecht; Politische Entscheidung; Abstimmungsregel; Neue politische Ökonomie